Power and Plenty Trade, War, and the World Economy in the Second Millennium - Findlay, Ronald; O'Rourke, Kevin H. (Princeton University Press, 2009)
International trade has shaped the modern world, yet until now no single book has been available for both economists and general readers that traces the history of the international economy from its earliest beginnings to the present day. Power and Plenty fills this gap, providing the first full account of world trade and development over the course of the last millennium. Ronald Findlay and Kevin O'Rourke examine the successive waves of globalization and "deglobalization" that have occurred during the past thousand years, looking closely at the technological and political causes behind these long-term trends. They show how the expansion and contraction of the world economy has been directly tied to the two-way interplay of trade and geopolitics, and how war and peace have been critical determinants of international trade over the very long run. The story they tell is sweeping in scope, one that links the emergence of the Western economies with economic and political developments throughout Eurasia centuries ago. Drawing extensively upon empirical evidence and informing their systematic analysis with insights from contemporary economic theory, Findlay and O'Rourke demonstrate the close interrelationships of trade and warfare, the mutual interdependence of the world's different regions, and the crucial role these factors have played in explaining modern economic growth. Power and Plenty is a must-read for anyone seeking to understand the origins of today's international economy, the forces that continue to shape it, and the economic and political challenges confronting policymakers in the twenty-first century
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Apr 2019)
Keywords: Geschichte 1000-2000; BUSINESS & ECONOMICS / Economic History; Globalization -- History; International economic relations -- History; International trade -- History; Geopolitik; Wirtschaftsentwicklung; Weltwirtschaft; Welthandel; Krieg